Compensation of parasitic elements of transistor in the class F amplifier with the tuning of impedances at harmonics - Yefymovych, A. P.; Krizhanovski, V. G. (Technology and design in electronic equipment, 2014)
The authors present a new method of construction and calculation of the output load circuit (OLC) for class F power amplifiers (PA) with the addition of the third harmonic of the voltage. This method allows compensating the negative influences of parasitic elements of transistor (output capacitance — COUT, and inductance — LOUT) on the drain efficiency of the amplifier. The circuit of the parasitic elements was considered as a part of the proposed OLC. To calculate the OLC a system of three algebraic equations was compiled. The system is solved numerically relative to the three parameters of the OLC, for which the impedance on a chip of the transistor (on COUT) for odd and even harmonics corresponds to the theory of class F PAs. This method is applicable for the calculation of the OLC, which is realized in the frequency range of 300–500 MHz, where the use of elements with lumped parameters only is not always possible, while using elements with distributed parameters leads to a substantial increase in the size of the whole amplifier. In the developed OLC, the authors used elements with both lumped and distributed parameters, thus achieving a compromise between the geometric dimensions and physical realizability of the circuit elements. The proposed OLC, taking into account the parasitic elements of the transistor, allows setting impedances independently at the first and third harmonics while maintaining impedance at the second harmonic tending to zero. This makes it possible to optimize the drain efficiency at a given level of output power. The efficiency 72.5% was experimentally obtained at POUT = 1.045 W for the class F amplifier running at 400 MHz. The proposed methodology for constructing and calculating the OLC can be used to implement class F power amplifiers in the integrated-circuit form.